If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -5 = 6x + 8 Reorder the terms: -5 + 5x = 6x + 8 Reorder the terms: -5 + 5x = 8 + 6x Solving -5 + 5x = 8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -5 + 5x + -6x = 8 + 6x + -6x Combine like terms: 5x + -6x = -1x -5 + -1x = 8 + 6x + -6x Combine like terms: 6x + -6x = 0 -5 + -1x = 8 + 0 -5 + -1x = 8 Add '5' to each side of the equation. -5 + 5 + -1x = 8 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = 8 + 5 -1x = 8 + 5 Combine like terms: 8 + 5 = 13 -1x = 13 Divide each side by '-1'. x = -13 Simplifying x = -13
| -9y= | | 7v*2-9v= | | -6z-z=7z-7-9z | | 10x-4=x-4 | | -x+8=21 | | -15x=10 | | 5b-8(1+8b)=-126 | | 18.10x=1.1 | | 11x+72=-126 | | 4(4x+4)=6(x-2) | | -x=-20 | | 28x^3+88x^2-37x-7=0 | | 58+6x=x-47 | | 1.8x-5.4=-5 | | 6(3+2x)-2=76 | | -41=37+6x | | -7-(-9)= | | 86=-8(3+2n)-2 | | 2x-3=4(x+2) | | 6x=2(8x+10) | | y+3=-7 | | 69y=34(2y+6) | | x-4y=27 | | 4-4=6x+5x | | 3.5x=18.10 | | 5x-20=10y | | 18.10x=3.5 | | 8=7t-11t | | p^2+16p+48=0 | | V^2-28=-3v | | -6=-7x | | n^2-12n+27=0 |